Studi Perlindungan Pantai Desa Larike Kabupaten Maluku Tengah - David D. M. Huwae; Lydia R. Parera (Syntax Corporation, 2023)
This study aims to analyze and understand the characteristics of the waves that hit the coastal wall of Larike Village and analyze an effective coastal protection system as an alternative to protecting the coast. The research was conducted on the beach of Larike Village, Central Maluku Regency. Survey research methodology and direct field observation, wave forecasting based on wind data using the Shore Protection Manual method with the help of Windrose Software. Extreme wave heights at certain periods can be determined using the Gumbel distribution method, while the effects of sea level fluctuations (tide and ebb) are analyzed using the Admiralty method. The results showed that the maximum wave height in the deep sea (Ho) was 2.60 m, wavelength (L) 35.679 m and, speed (C) 4.789 m/s in the period (T) 6.70 seconds from the southwest. The best security alternative is obtained in the form of a rubble mound breakwater structure placed at a depth of -5 m with a distance from the shoreline (y) = 70 m, length L of the building = 134 m, and gap width (b) = 50.60 m giving a reflection of 30 %, absorbing 51.8% of wave energy and 18.2% of transmitting waves.